2016
DOI: 10.1016/j.jvs.2015.04.387
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic properties of human placenta-derived adherent cells and efficacy in hindlimb ischemia

Abstract: PDACs exhibited various activities consistent with angiogenesis and tissue repair, supporting the continued investigation of this cell therapy as treatment for vascular disease-related indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 32 publications
5
23
0
Order By: Relevance
“…However, the patients who had an increase in ABI had a notable change following the administration of cenplacel that continued through the long-term follow-up. This durable effect that occurred shortly after dosing suggests that cenplacel could have a therapeutic effect on the peripheral vasculature similar to the observations in the pre-clinical animal model (13), and awaits confirmation in a phase 2 study.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…However, the patients who had an increase in ABI had a notable change following the administration of cenplacel that continued through the long-term follow-up. This durable effect that occurred shortly after dosing suggests that cenplacel could have a therapeutic effect on the peripheral vasculature similar to the observations in the pre-clinical animal model (13), and awaits confirmation in a phase 2 study.…”
Section: Discussionsupporting
confidence: 58%
“…Animals treated with cenplacel demonstrated decreased limb necrosis with enhanced vascular collateralisation effects as evidenced by enhanced perfusion when measured by Doppler-enhanced ultrasound, and by angiographic imaging of the affected limb. Histological analysis revealed enhanced maturation of blood vessels in animals treated with cenplacel (13).…”
Section: Key Messagesmentioning
confidence: 96%
See 1 more Smart Citation
“…It is important to note that CsA blocks recipient T‐lymphocyte reactions , and compromises granulocyte migration during acute inflammation. When hMSCs are IM‐transplanted in immunocompetent animals, a short dwell time of 4–8 days has been reported by Prather et al , Francki et al , and Hamidian Jahromi et al . Exceptions are the studies by Mao et al and Shabbir et al who reported therapeutic effects for 4 weeks that may infer survival of IM‐transplanted hWJ‐MSC or pBMMSCs in immunocompetent SD‐rats and TO2 hamsters respectively, although more probably reflect the “hit‐and‐run” mechanism by which MSCs are considered to have their effects .…”
Section: Dwell Time Of Im‐delivered Mscsmentioning
confidence: 99%
“…Similarly, Francki et al IM‐delivered placenta‐derived adherent cells, luciferase‐transduced, in the ischemia‐induced hind limb muscle of BalbC mice 24 hours after injury, and reported significant improvement in the blood flow and vascular density by 35–49 days. Furthermore, at 49 days, the injured muscle showed a reduction of inflammatory infiltrate and improvement in the structure of the regenerated muscle fibers . Beegle et al, in a similar CLI model, IM‐transplanted hBMMSCs over‐expressing VEGF in the hamstrings of immunocompromised NOD/SCID‐IL2Rγ−/− (NSG) mice.…”
Section: Preclinical Studies: Im‐delivered Mscs To Treat Local Patholmentioning
confidence: 99%